2005
DOI: 10.1097/00000542-200501000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Response Properties and Receptive Fields of Spinal Dorsal Horn Neurons in Rats after Surgical Incision in Hairy Skin

Abstract: The results suggest that wide-dynamic-range neurons are responsible for behavioral hyperexcitability after surgical incision but that HT neurons are not involved in the hyperexcitability, despite the fact that HT neurons are capable of responding to innocuous stimuli by reversal of gamma-aminobutyric acid-mediated inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 0 publications
3
19
0
Order By: Relevance
“…During incision and suturation an increase in activity was recorded in all three classes of spinal neurons, but spontaneous activity and that evoked by light tactile stimulation, as is used to assess allodynia, for several hours after surgery was only prominent in the WDR neurons (Kawamata et al, 2005). Both primary and secondary tactile allodynia were apparent from 30 min to 3-4 days after surgery, in agreement with our own findings in rat hairy skin after an almost identical incision.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…During incision and suturation an increase in activity was recorded in all three classes of spinal neurons, but spontaneous activity and that evoked by light tactile stimulation, as is used to assess allodynia, for several hours after surgery was only prominent in the WDR neurons (Kawamata et al, 2005). Both primary and secondary tactile allodynia were apparent from 30 min to 3-4 days after surgery, in agreement with our own findings in rat hairy skin after an almost identical incision.…”
Section: Discussionsupporting
confidence: 88%
“…We and others have previously shown that central sensitization appears after incision in rat hairy skin, as evidenced by the actions of systemic local anesthetics on post-incisional pain (Duarte et al, 2005) and by recordings from high threshold and low threshold afferents as well as wide dynamic range (WDR) spinal cord neurons (Kawamata et al, 2005). During incision and suturation an increase in activity was recorded in all three classes of spinal neurons, but spontaneous activity and that evoked by light tactile stimulation, as is used to assess allodynia, for several hours after surgery was only prominent in the WDR neurons (Kawamata et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…Plantar paw incision causes a rapid, transient release of glutamate and aspartate in the spinal cord for the first hour after incision [48], and intrathecal delivery of antagonists of AMPA/kainate receptors [26,31] and of mGluR5 receptors [50], but antagonists of NMDA receptors [47], around the time of incision can reduce the pain elevated by paw incision. These findings suggest that the activation of AMPA/kainate and certain metabotropic glutamate receptors in the spinal cord is important for the induction of pain after skin incision [23,44]. …”
Section: Discussionmentioning
confidence: 99%
“…The initial discharge of local nerves caused by the incision [46] and the later, delayed activation of impulses from peripheral nerve that may be conducted by injured or uninjured fibers [4,5,17,30] probably contribute to the establishment of longer-lasting hyperalgesia [28], and there is little doubt that changes in the central nervous system (CNS), at least at the spinal cord (and probably also in the brain), are essential for the maintained chronic pain [10,23,24]. The differential ability of different drugs, applied at the incision site or delivered systemically, to prevent or reverse postoperative pain supports the concept of at least 2 stages of postoperative pain, an induction stage and a maintenance stage, which involve different mechanisms and occur at different locations [2,12,27].…”
Section: Introductionmentioning
confidence: 99%
“…19 32 and increases the sensitivity of WDR neurons to both noxious and non-noxious inputs. 31 These are the first and fundamental steps of central sensitisation. The overall effect is an increased number of action potentials generated in nociceptive pathways ascending to neuromatrix regions.…”
Section: A Peripheral Nociceptorsmentioning
confidence: 99%